Transformation of the Political Regime in Modern Russia: Forecasting and Management in the Paradigm of Sovereign Transit - Denis Viktorovich, Potapov (International Journal of Psychosocial Rehabilitation, 2019)
The article is devoted to summarizing the results of a comprehensive study by the author of the political regime transformation in modern Russia. It is based on the assumption that for planning and managing the political regime transformation in modern Russia, it should be considered in the paradigm of sovereign (rather than democratic) transit. The study proved for the first time the conditionality of the crisis of the democratic transit paradigm by erosion of the democratic institutions of economically developed countries of the West; the ideological component of the transformation of political regimes is investigated; the complex of subject-object relations of the Russia political regime transformation is considered. The assessment of the prospects of gaining by Russia the national subjectivity of the political regime; the concept of “sovereign transit paradigm” is introduced into scientific circulation. The international experience of changing ideologies as a tool for transforming the political regime is analyzed. The basic elements of the planning system and the management of the transformation of the political regime of modern Russia in the sovereign transit paradigm are described; the choice of the ideology that is most relevant for Russia at the present stage of the transformation of the political regime is substantiated